2010
DOI: 10.17305/bjbms.2010.2728
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) as an Acute Phase Reactant in Patients on Chronic Hemodialysis

Abstract: Lipoprotein (a) [Lp(a)], is an independent risk factor for atherosclerotic cardiovascular disease in patients on chronic hemodialysis. A low concentration of high density lipoprotein cholesterol (HDL-C) and serum albumin are another potential risk factors. e purpose of this study was to explore in patients on chronic hemodialysis, whether Lp(a) elevated levels are infl uenced by activated acute phase response (APR) and the correlation of Lp(a) with HDL-C and serum albumin. In  hemodialysis patients with C-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 55 Several studies have suggested a strong association between increased Lp(a) and cardiovascular disease, including stroke, and aortic stenosis. 56 Also, Lp(a) was shown to be positively correlated with interleukin (IL)‐6 and CRP after acute myocardial infarcts, 57 , 58 indicating its involvement in immune and pro‐inflammatory responses. Similar to sdLDL‐C, in the present study, we also found that TA patients had a higher Lp(a) level than the healthy participants and that Group I had higher Lp(a) levels than Groups II and III, indicating that serum Lp(a) levels are associated with TA severity.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Several studies have suggested a strong association between increased Lp(a) and cardiovascular disease, including stroke, and aortic stenosis. 56 Also, Lp(a) was shown to be positively correlated with interleukin (IL)‐6 and CRP after acute myocardial infarcts, 57 , 58 indicating its involvement in immune and pro‐inflammatory responses. Similar to sdLDL‐C, in the present study, we also found that TA patients had a higher Lp(a) level than the healthy participants and that Group I had higher Lp(a) levels than Groups II and III, indicating that serum Lp(a) levels are associated with TA severity.…”
Section: Discussionmentioning
confidence: 99%
“…In RA patients Lp(a) was associated with elevated CRP-level and erythrocyte sedimentation rate (ESR) and therefore playing an important role in the acute phase cascade reaction process [23] Lp(a) is claimed to react as acute phase protein in other diseases as well esp. ischemic stroke [43] vestibular neuronitis [44], in patients on chronic haemodialysis [45, 46] and polymyalgia rheumatica [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 20–30% of the world’s population have an elevated Lp(a), defined as > 50 mg/dL or > 125 nmol/L [ 17 ]. There are exceptions to generally stable levels, including a stressful environment such as sepsis, in which Lp(a) levels are acutely elevated [ 18 , 19 ]. Normal lifestyle activities such as diet, exercise, and weight loss have limited effect on Lp(a), and lipid medications, such as statins, may modestly raise Lp(a) levels [ 20 , 21 ].…”
Section: Lp(a) and Antifibrinolytic Effectsmentioning
confidence: 99%